Management of Prosthodontic Rehabilitation in a Patient with Aggressive Periodontitis and Metabolic Dysfunction-Associated Steatotic Liver Disease Using the “All-on-6” Concept - Symonenko Рената; Trehubenko Ангеліна; Soloviova Галина; Makovei Ярослав (Actual Dentistry, 2026)
Background. Periodontitis is increasingly being linked to an individual’s general health status [1, 2, 3]. The prosthetic rehabilitation of patients with generalized periodontitis and metabolic dysfunction-associated steatotic liver disease (MASLD) represents a highly relevant and challenging task, given the high prevalence and comorbidity of these two conditions. Case Report. This article presents a clinical case of comprehensive rehabilitation of a 32-year-old patient with aggressive periodontitis complicated by partial tooth loss and MASLD. The clinical picture was characterized by severe inflammation in the periodontal tissues, periodontal pockets 6–7 mm deep, grade II–III tooth mobility, and significant alveolar bone resorption (exceeding ⅔ of the root length according to CT data). Additional laboratory and instrumental investigations revealed impaired carbohydrate and lipid metabolism, as well as moderate hepatic steatosis (S2) without signs of fibrosis (F0) based on steatometry and elastography data. The microbial profile of the periodontal pockets consisted predominantly of Haemophilus parainfluenzae (106 CFU) and Fusobacterium nucleatum (106 CFU) [4–6]. Rehabilitation was carried out using a multidisciplinary approach involving a dentist, an endocrinologist, and a gastroenterologist. It included oral sanitation, targeted antimicrobial and anti-inflammatory therapy, microbiome normalization, and the correction of metabolic disorders and patient lifestyle. Following the stabilization of the patient’s general somatic status, a staged implantation according to the “All-on-6” concept was performed, featuring immediate loading with temporary adaptive screw-retained prosthetic constructions. Results. The treatment resulted in the stabilization of metabolic parameters, a reduction in the inflammatory process activity, and the creation of favorable conditions for implant osseointegration. Conclusions. The proposed approach demonstrates the high efficacy of comprehensive treatment for patients with severe forms of periodontitis presenting against a background of metabolic disorders, emphasizing the necessity of multidisciplinary interaction to achieve predictable outcomes.